1988
DOI: 10.1007/bf01870450
|View full text |Cite
|
Sign up to set email alerts
|

Apical Na+ permeability of frog skin during serosal Cl− replacement

Abstract: Gluconate substitution for serosal Cl- reduces the transepithelial short-circuit current (Isc) and depolarizes short-circuited frog skins. These effects could result either from inhibition of basolateral K+ conductance, or from two actions to inhibit both apical Na+ permeability (PapNa) and basolateral pump activity. We have addressed this question by studying whole-and split-thickness frog skins. Intracellular Na+ concentration (CcNa) and PapNa have been monitored by measuring the current-voltage relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…With serosat gluconate, studied by us in whole skins, effects were insignificant or minimal, despite marked cell depolarization. Leibowich et al (1988) have reported similar findings in whole skins; in isolated epithelia, on the other hand, serosal gluconate regularly inhibited the short-circuit current. On the basis of analysis of the apical amiloride-sensitive currentvoltage relationship, it was concluded that serosal gluconate does not inhibit either apical Na permeability or the basolateral Na pump, but likely reduces cell volume, triggering inhibition of basolateral K channels.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…With serosat gluconate, studied by us in whole skins, effects were insignificant or minimal, despite marked cell depolarization. Leibowich et al (1988) have reported similar findings in whole skins; in isolated epithelia, on the other hand, serosal gluconate regularly inhibited the short-circuit current. On the basis of analysis of the apical amiloride-sensitive currentvoltage relationship, it was concluded that serosal gluconate does not inhibit either apical Na permeability or the basolateral Na pump, but likely reduces cell volume, triggering inhibition of basolateral K channels.…”
Section: Discussionsupporting
confidence: 68%
“…Other substitution experiments have pointed to basolateral NaCI cotransport (Ferreira & Ferreira, 1981;Giraldez & Ferreira, 1984;D6rge et al, 1985), whereas studies of volume regulation have suggested basolateral NaKC12 cotransport (Ussing, 1985). On the other hand, isotope kinetic studies of Stoddard, Jakobsson and Helman (1985) have indicated electroneutral basolateral CI transport, for the most part uncoupled to transport of either Na or K. Cellular electrical effects of serosal CI removal have been described by Biber et al (1985), by Duffy et al (1986), and by Leibowich, DeLong and Civan (1988), Our findings provide additional information concerning membrane electrophysiology and cell cation activities.…”
Section: Discussionmentioning
confidence: 93%
“…Effects of serosal tonicity and Cl" re placements on transepithelial Na+ transport have been the subject of several studies [7][8][9][10]. Microelectrode experiments [7][8][9] showed that a major part of the inhibition on Na+ transport following Cl" removal or after elevation of the serosal osmolality could be attributed to cell depolarization. This depo larization of the intracellular potential was found to be caused by a reduction of the basolateral K+ conductance.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline pulsing was periodically interrupted to impose a sequence of voltage pulses across the skin. Each train comprised 12 pairs of alternately hyperpolarizing and depolarizing pulses, the magnitude increasing by 20 mV in successive steps (DeLong & Civan, 1984;Leibowich, DeLong & Civan, 1988). Data were acquired with pulse durations of 16 or 32 msec and interpulse intervals of 240-640 msec, but the choice of pulse duration is not critical (Civan et al, 1989).…”
Section: Intracellular Measurementsmentioning
confidence: 99%
“…Insofar as Cd =+ is thought to reduce the apical C1-conductance of frog skin (Hayashi et al, 1977), these experiments were performed with skins bathed with the standard Ringer's solution on their serosal surfaces, but with an equimolar replacement of NO3 for Clon their mucosal surfaces. This approach has been empirically used in studies of frog skin to reduce the baseline, non-Na + conductance (Nagel, GarciaDiaz & Essig, 1983;Civan et al, 1987;Leibowich et al, 1988).…”
Section: Approaches For Altering Cytosolic Activity Of Ca 2+mentioning
confidence: 99%